A fabrication history based strain‐fatigue model for prediction of crack initiation in a radial loading wheel. Issue 11 (29th March 2017) - Zhao, Y.; Ma, M.; Qin, R.; Ling, Y.; Wang, G.; Wan, X.; Gu, H.; Liu, Y.
Abstract: A strain‐based fatigue model concerning fabrication history is applied to predict the fatigue life of a commercial car wheel under radial loads. As the prior conditions, the strain fatigue testing is performed on standard specimen of DP590 and FB540 steels at various fabrication states, including raw materials, pre‐strain and pre‐strain + bake. Furthermore, the strain distribution of car wheel during its rotation under radial loads is simulated via ANSYS. The fatigue properties mainly determined by crack initiation of car wheels at various fabrication states are predicted via local stress–strain method, in which the scale and surface factors are also taken into account. The radial fatigue testing is carried out, and the results are used to validate the present model. The fracture mechanism is analysed using FEI Nova 400 field emission gun scanning electron microscope.